Application of Academic Supervision through an In House Training (IHT) Approach to Increase Teacher Professionalism at SMP Santa Lucia Sei Rotan - Hotmaida Sidabutar; Nathanael Sitanggang; Wildansyah Lubis; Rosnelli Rosnelli (Budapest International Research and Critics University, 2023)
SMP Santa Lusia Sei Rattan is one of the secondary schools that has an in-house training supervision program and policy involving several education personnel, administrative staff, office boys and also several teachers, but the implementation of this supervision is not entirely successful, because this supervision is only ceremonial that spends the budget, but after supervision the teacher's attitude and actions are still not in accordance with the determination of procedures and standards predefined work. As a result, there are still many teachers, as well as other educators who have attitudes that are not in accordance with what is expected, and the abilities of teachers do not develop, so that the supervision and improvement activities carried out are in vain. The research method used is a qualitative descriptive research method with a literature study method. The results of the study explain that what must be done by leaders in supervising in-house training, namely by setting the vision, mission and goals to supervise, organizing supervisory teams, planning and scheduling supervision, observing classes and teaching materials, providing support and coaching by leaders, coordinating for in-house training supervision and evaluating and monitoring programs that have been carried out at Santa Lusia Sei Junior High School Rattan. Leaders should set vision, mission, and goals for the in-house training supervision they will supervise, as well as organize the supervisory team, plan and schedule supervision, observe classes and teaching materials, offer support and coaching to leaders, coordinate in-house training supervision, and evaluate and monitor programs that have been implemented at Santa Lusia Sei Rattan Junior High School.